Investigation of single-shot beam quality measurements using state of the art solid-state dosimeters for routine quality assurance applications in mammography. (August 2021) - Bemelmans, Frédéric; Marshall, Nicholas W.; Dedulle, An; Tri Wigati, Kristina; Ivanovic, Sonja; Binst, Joke; Struelens, Lara; De Hauwere, An; Devillers, Magali; Bosmans, Hilde
Highlights: Medical physicists should verify new dosimetry devices for the conditions during any physics tests. The energy response of tested solid state dosimeters was excellent (25kVp-32kVp). Tested solid state dosimeters are trustworthy for routine QA purposes (output-HVL). Abstract: Purpose: To assess if single shot acquisitions with solid-state dosimeters as well as Robson's method could replace ionization chambers for tube output and HVL measurements, saving medical physicists time. Material and methods: The energy responses of 4 solid-state dosimeters with automatic calculation of HVL were compared to ionization chamber measurements. Five anode/filter combinations were tested: Mo/Mo, Mo/Rh, Rh/Rh, W/Rh and W/Ag, from 24kVp to 35kVp. Tube output was measured free in air. HVL was measured using the solid-state dosimeters (single-shot acquisition), then manually with aluminum sheets and finally using the parametrization method of Robson. Results: Deviations in tube output and HVL related to energy response in SSD were small in the 25–32 kVp range, and for tube output typically within 3%. Extrapolation using the Robson parametrization was within 5%, except for one device and for all W/Rh. Deviations of the HVL using the single shot approach were within 10% of the gold standard data. Larger deviations were found at the extreme tube voltages of 24kVp and 35kVp (maximum of 24%). Conclusion: With the assumption that deviations in tube output of 5% and for HVL of 10% are acceptable, all tested solid state dosimeters met this criterion in the tube voltage range of 26kVp to 32kVp. Robson's method worked well for the spectra for which the method was developed, making both alternative approaches trustworthy for routine quality assurance purposes.